Translating Gamification from Digital Technology to Analog Systems in Design Education - Alvanov Zpalanzani Mansoor; Gabrielle Ivy Luna Putri (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study examines the translation of gamification principles from digital technology into analog systems within higher education, focusing on a design criticism class. Using a qualitative Design-Based Research approach, the study followed stages of analysis, design, implementation, and evaluation. Data were collected through literature review, documentation of design artifacts, questionnaires administered to 75 students, and semi-structured interviews with 10 purposively selected participants. Thematic analysis combined with descriptive statistics revealed that analog gamification enhances motivation, participation, collaboration, and enjoyment in classroom learning. However, the findings also highlight ambivalent effects, including risks of social pressure, verbal participation bias, and distraction when mechanics lack inclusivity and transparency. The study concludes that gamification effectiveness depends not only on game mechanics but also on system design quality, instructor facilitation, and the learning environment. The implications recommend developing inclusive, adaptive, and academically substantive analog gamification models to strengthen engagement and achievement in design education.